Factorial design study of self-management using Dnurse App in T2DM patients - Tang, Hongxia; Tan, Huiwen; Zhang, Jihong; Zhang, Mingjiao; Chen, Mengjie; Kong, Laixi; Wang, Xiaoxia; Guo, Maoting; Zhao, Jinxiu; Song, Lili; Zheng, Zijun; Yang, Huiqi; et al. (Frontiers in Endocrinology, 2025)
BackgroundWith the popularity of smart phones and the development of information technology, more and more patients are adopting diabetes APPs for self-management. However, at present, there are few research reports on the effect of those APPs coming from China.ObjectiveThe purpose of this study was to evaluate the effectiveness and applicability of an APP for blood glucose control that is widely popular among Chinese patients with type 2 diabetes mellitus (T2DM).MethodsThis is a 2-center, factorial design, with equal proportional distribution, and superiority trial conducted in outpatient endocrinology clinics at two tertiary hospitals in Chengdu, China. The trial enrolled smartphone-literature individuals aged at least 18 years old who have been diagnosed with T2DM based on glycosylated hemoglobin A1c (HbA1c) of at least 7.0%. The subjects were randomly divided into 4 groups, which were the usual care group (G1); the telephone follow-up group (G2); the APP group (G3); the APP & telephone follow-up group (G4). After 6 months of these interventions, the primary outcome was HbA1c, and the secondary outcomes were blood pressure (BP), body mass index (BMI), frequency of self-monitoring of blood glucose (SMBG), and satisfaction with the APP.Results273 patients with type 2 diabetes were included in the study, among which 226 (82.8%) were followed up at the 3rd month and 220 (80.6%) at the 6th month. There was no significant difference in HbA1c attainment rate among the four groups after intervention (P >.05), but the HbA1c attainment rate in the two APP groups was higher than that in the other groups. The systolic blood pressure (SBP) of the two APP groups was significantly lower than that of the other groups (P <.05). There was no significant difference in the compliance rate of SMBG among the four groups (P >.05). Each item of the participants’ satisfaction evaluation of the APP scored more than 4.5 points.ConclusionsThe diabetes APP has a tendency to improve the HbA1c compliance rate of T2DM patients. The APP can help reduce patients’ BP, and patients have a high satisfaction evaluation of the APP. Therefore, the study supports the use of the APP for self-management in people with type 2 diabetes.Clinical Trial Registrationhttps://www.chictr.org.cn, identifier ChiCTR2100042297.